The empirical investigation: Performance of Socially Responsible and Energy sector funds - Ylitalo, Ville (My University, 2022)
This study examines the performance of socially responsible mutual funds in the market compared to the performance of mutual funds in the energy sector. The funds selected for research in both sectors are listed on the U.S. market, with the allocation of funds naturally often global. Social responsibility in the day-to-day running of companies and funds is on the rise and a big topic and has led to strong growth of socially responsible and ethical investment products as they become a good investment target or part of a portfolio alongside traditional funds and investment products. Investors, stakeholders and society require companies to take action in a diverse field of responsibility. The energy sector, which is generally considered to be a polluting, less responsible industry, was chosen as the reference group for the study. However, the energy sector cannot be blamed for its ongoing and responsible actions. The study's primary goal is to find out how socially responsible investment funds (SRIs) have performed over time in relation to the energy sector. If viewed from a theoretical perspective, SRI financial investments may lead to lower risk-adjusted returns. This is due to the limited investment and diversification potential when funds can only be invested in qualifying investments. The study used an extensive and comprehensive sample of mutual funds obtained from Datastream database from February 2005 to October 2021. The data included the daily quotations of the funds. The selected funds are the largest and most popular in both sectors, and an attempt was made to keep the total amount of funds managed close together.Multifactor models were chosen to explain the daily returns of mutual funds. These models used in the study are the CAP model, the Fama-French 3-factor and 5-factor models, and the Carhart 4-factor model. In addition to these, performance was assessed using a risk-adjusted Sharpe meter and Jensen's Alpha. Based on the study results, socially responsible investment funds outperformed those in the energy sector, with results often but not always statistically significant. The shorter the period under review, the better the returns for socially responsible funds, but the significance decreased significantly during the shorter periods.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance